Integration of precision medicine into the dental care setting - Steigmann, Larissa; Kačarević, Željka Perić; Khoury, Jessica; Nagy, Katalin; Feres, Magda (Frontiers in Dental Medicine, 2024)
This narrative review aims to discuss the incorporation of novel medical concepts and tools into dental practice, with the goal of improving early diagnosis and exploring new personalized treatment options for oral pathologies, such as caries and periodontitis. Preventative dental approaches concentrate on the timely detection of oral infections and the integration of biomarker analysis to recognize pathogenic changes at early stage of disease. Likewise, periodic monitoring after the treatment is relevant to ensure the balance in the oral biofilms and prevent relapse. Additionally, more attention has shifted towards the contributing factors to disease development, such as essential nutrients. Sufficient levels of vitamin C, vitamin D and zinc pre- and post-operatively are employed to boost immune function and reduce the risk of postoperative infections. Omega-3 fatty acids, melatonin, and antioxidants like vitamin E, which have anti-inflammatory properties, are utilized to help minimize excessive inflammation and promote faster recovery. The data presented in this manuscript emphasize the crucial integration of innovative healthcare concepts and tools into dental practices. By adopting a more holistic view of the patient, clinicians can tailor treatments to each individual's predispositions, lifestyle, and oral health conditions. This review also highlights the potential of salivary biomarkers and point-of-care technologies in enhancing early diagnostic accuracy and personalizing treatment. Bridging the gap between oral and systemic health is the most effective approach to improving patient quality of life. These findings underscore the importance of continued interdisciplinary collaboration in dentistry.